HUBUNGAN KONFLIK PERAN GANDA PADA WANITA BEKERJA DENGAN KEHARMONISAN RUMAH TANGGA - Fitria Panduwinata, Vina; Hartono, Roni; Atmasari, Ayuning (Fakultas Psikologi - Universitas Teknologi Sumbawa, 2019)
This research aimed at knowing correlation between conflict and role af women as working mom with domestics harmony. It was conducted at rural village Moyo Mekae, Sub-distrid Moyo Hilir, Distritc Sumbawa. It has fourty sample of  working moms as civil servants. Research data was taken by using scale conflict instrument and domestic harmony instrument. This research used quantitative research  method correlational. Correlational research aimed at knowing strength and the correlation within variables. By this research is taken  information concerning correlational feedback, not cause-effect. The result showed that there are significant correlation between conflict working mom and domestic harmony. It has coofecient correlation between  two variabels as r = -0,672; p= 0,0001 (p<0,05). Generally based on average counting, it has strong value. Based on scale conflict of working mom, it has high value, time based conflict has 4,325 than the other aspects. This showed that conflict because of time as considerably aspect to build relation. Therefore, domestics harmony has highes value to create religious life. It has 4,20. It showed that the domestic harmonys could be created through religious life.